The Choice of Laboratory Methodology Influences Autoantibody Test Results - Rönnelid, Johan (Frontiers in Immunology, 2015)
During the last 25 years clinical autoantibody determinations have changed dramatically. Old and slow techniques with high diagnostic specificity have been replaced with automated and faster techniques that most often have a higher diagnostic sensitivity at the expense of a lower diagnostic specificity. Newer techniques are mostly quantitative, allowing for follow-up of autoantibody levels. Whereas the older procedures utilized autoantigens in soluble and native states, most modern techniques rely on autoantigens attached to surfaces, with the risk of exposure of denatured epitopes. Comparisons between antibody measurement techniques can be obtained from the results of external quality assessment programs. Yet as the main objective for external quality assessment is the monitoring of clinical laboratories they cannot focus on the kind of low-level and often polyreactive sera which are common in the real world and in which a single definite target response cannot be easily defined. Such common sera are very useful, however, for analysis of differences between autoantibody measurement techniques. The European Consensus Finding Study Group on Autoantibodies has been working with this approach for 28 years.